Clinical characteristics and risk factor analysis of overlapping syndromes of COPD-OSA with metabolic syndrome in middle-to-high altitude areas - Qin, Yisha; Aju, Aniu; Wan, Yilin; Song, Mengchen; Hao, Xingxing; Li, Jiwu; Shi, Xuefeng (Frontiers in Medicine, 2025)
ObjectiveTo investigate the clinical characteristics and risk factors of overlap syndrome (OVS) patients with metabolic syndrome (Mets) in middle-high altitude areas.MethodsA retrospective analysis was performed on adult (≥40 years) OVS patients and healthy controls from Qinghai Provincial People’s Hospital (January 2017–January 2024), including general and laboratory data.Results1. OVS patients had a higher rate of Diabetes, Hypertension, and Pulmonary Hypertension than healthy individuals; 2. OVS patients had significantly higher levels of inflammatory markers, hematologic, and lipid than Healthy individuals; 3. The proportion of OVS patients who also had Mets was 55.24%; 4. Compared to OVS patients without Mets, OVS patients with Mets had significantly higher levels of neutrophils, hemoglobin, red blood cell distribution width, C-reactive protein, NHR, and NLR, as well as a higher percentage of time with pulse oxygen saturation (SpO2) less than 80%, while the average and lowest SpO2 were significantly lower; 5. Hypoxic index, average SpO2, baseline SpO2, SpO2 less than 90%, and SpO2 less than 80% may be risk factors for the co-occurrence of OVS and Mets; 6. The rate of Mets among OVS patients who lived at an altitude of ≥2,500 meters was 63.79%, higher than OVS patients who lived at an altitude of <2,500 meters (44.68%).ConclusionOver half of middle-high altitude OVS patients have Mets, with higher rates at higher altitudes. Hypoxia may drive OVS-Mets comorbidity, while inflammation appears less significant.